Haemopedia RNA-seq: a database of gene expression during haematopoiesis in mice and humans. Issue Volume 47:Issue D1(2019) (5th November 2018) - Choi, Jarny; Baldwin, Tracey M; Wong, Mae; Bolden, Jessica E; Fairfax, Kirsten A; Lucas, Erin C; Cole, Rebecca; Biben, Christine; Morgan, Clare; Ramsay, Kerry A; Ng, Ashley P; Kauppi, Maria; et al.
Abstract: During haematopoiesis, haematopoietic stem cells differentiate into restricted potential progenitors before maturing into the many lineages required for oxygen transport, wound healing and immune response. We have updated Haemopedia, a database of gene-expression profiles from a broad spectrum of haematopoietic cells, to include RNA-seq gene-expression data from both mice and humans. The Haemopedia RNA-seq data set covers a wide range of lineages and progenitors, with 57 mouse blood cell types (flow sorted populations from healthy mice) and 12 human blood cell types. This data set has been made accessible for exploration and analysis, to researchers and clinicians with limited bioinformatics experience, on our online portal Haemosphere:https://www.haemosphere.org . Haemosphere also includes nine other publicly available high-quality data sets relevant to haematopoiesis. We have added the ability to compare gene expression across data sets and species by curating data sets with shared lineage designations or to view expression gene vs gene, with all plots available for download by the user.